Peri-intraventricular hemorrhage and oxidative and inflammatory stress markers in very-low birth weight newborns - Jamil P.S. Caldas; Carolina A. Braghini; Taís N. Mazzola; Maria M.S. Vilela; Sérgio T.M. Marba (Elsevier, 2015)
OBJECTIVES: To evaluate the association between oxidative and inflammatory stress markers with peri-intraventricular hemorrhage (PIVH) in very-low birth weight newborns.METHODS: This was a prospective study conducted in a level III neonatal unit. Basal and stimulated reactive oxygen intermediates (ROIs), reduced glutathione (GSH), and interleukin-6 (IL-6) levels were measured in umbilical cord blood. Newborns underwent serial ultrasound at the bedside, at 6, 12, 24, and 72 hours of life and at seven days for the diagnosis of PIVH, classified as grades I to IV. Two groups were assessed, those with and without PIVH; maternal and neonatal control variables were used for comparison. Univariate and multiple regression analyses were applied.RESULTS: A total of 125 newborns were assessed. PIVH incidence rate was 12.0%. In the univariate analysis, basal ROI, the use of two or more doses of corticosteroids, birth weight < 1,000 g, ventilatory support use, and SNAPPE II value ≥ 22 were significantly associated with PIVH. However, in the multivariate analysis, only antenatal steroid use was independently associated with the disease (OR 0,194; 95% CI: 0,048 to 0,773; p=0,02).CONCLUSION: ROI, GSH, and IL-6 levels were not associated with the occurrence of PIVH in very-low birth weight infants